Effect of Bedrock Morphology, Axial Transport and Lateral Material Sources on Braided River Sediments: A Case Study from Munin Valley, Central Spitsbergen - Ondráčková, Lenka; Nývlt, Daniel; Hanáček, Martin (Polish Polar Research, 2020)
The Munin River (Svalbard) is a mountainous braided proglacial river. It drains from two valley glaciers developing an elongated channel belt and turning into a wide braided outwash fan before entering the main river. The Munin River is in its axial head supplied by the material from glaciers, and along the stream by material from lateral sources, i.e. braided outwash fan, debris-flow and fluvial-flow dominated fans. Detailed analyses of clast roundness showed that roundness suddenly changes to higher degrees in negative correlation with channel belt width and sinuosity of the channels. The roundness increases rapidly in sections with small channel belt width and low sinuosity, which can be seen in the bedrock gorge. On the contrary, the roundness does not change much in sections with large channel belt width and high sinuosity. The morphological changes of the channel belt are controlled by the bedrock morphology of the catchment, which is the main factor affecting the clast roundness in the Munin River. The nature of the lateral material sources and the downstream traction affect rather the individual gravel fractions.